A new multicollinearity diagnostic for generalized linear models - Huang, Chien-Chia L.; Jou, Yow-Jen; Cho, Hsun-Jung (My University, 2016)
We propose a new collinearity diagnostic tool for generalized linear models. The new diagnostic tool is termed the weighted variance inflation factor (WVIF) behaving exactly the same as the traditional variance inflation factor in the context of regression diagnostic, given data matrix normalized. Compared to the use of condition number (CN), WVIF shows more reliable information on how severe the situation is, when data collinearity does exist. An alternative estimator, a by-product of the new diagnostic, outperforms the ridge estimator in the presence of data collinearity in both aspects of WVIF and CN. Evidences are given through analyzing various real-world numerical examples.
Keywords: Collinearity; condition number; diagnostic; generalized linear models; variance inflation factor